New horizons in the understanding of the causes and management of diabetic foot disease: report from the 2017 Diabetes UK Annual Professional Conference Symposium. Issue 3 (23rd January 2017) - Clokie, M.; Greenway, A. L.; Harding, K.; Jones, N. J.; Vedhara, K.; Game, F.; Dhatariya, K. K.
Abstract: Diabetes‐related foot disease remains a common problem. For wounds, classic teaching recommends the treatment of any infection, offloading the wound and ensuring a good blood supply, as well as ensuring that the other modifiable risk factors are addressed and optimized. There remain, however, several questions about these and other aspects of the care of diabetes‐related foot disease. Some of these questions are addressed in the present report; in particular, the impact of newer technologies in the identification of any organisms present in a wound, as well as the use of novel approaches to treat infections. The use of new remote sensing technology to identify people at risk of developing foot ulceration is also considered, in an attempt to allow early intervention and prevention of foot ulcers. The psychological impact of foot disease is often overlooked, but with an increasing number of publications on the subject, the cause‐and‐effect role that psychology plays in foot disease, such as ulcers and Charcot neuroarthropathy, is considered. Finally, because of heterogeneity in diabetic foot studies, comparing results is difficult. A recently published document focusing on ensuring a standardized way of reporting foot disease trials is discussed. What's new?: Foot disease is relatively common in people with diabetes. Newer technologies for the management of wound infections are on the horizon. Remote sensing technologies are being developed to allow identification of at‐risk tissues at an early stage, allowing timely intervention and prevention of foot wounds. The psychological impact of foot disease is often under‐appreciated but has a potentially significant role in cause and effect on ulcers and Charcot neuroarthopathy. Comparing outcomes of published trials in foot disease has been difficult because of the lack of standardization. A framework for reporting standards has recently been published to help overcome this.